Disaster Prevention Management Governance Model Forest and Land Fires Based on Ecotourism in Riau - Syamsuadi, Amir; Yahya, MHD Rafi; Anugerah, M Fajar; Farras, Aqil; Trisnawati, Liza; Elvitaria, Luluk (JIM - Journal International Multidisciplinary, 2024)
Riau Province is one of the regions in Indonesia that frequently experiences forest and land fires, which cause economic losses, environmental damage and threats to public health. This research aims to build a model for preventing forest and land fire disasters through an ecotourism approach, with a focus on integrating conservation efforts and empowering local communities. The research method used is a qualitative approach with case studies in several ecotourism areas in Riau. Data was collected through in-depth interviews with stakeholders, field observations, and analysis of related documents. The research results show that ecotourism has significant potential in preventing forest and land fires, especially through increasing environmental awareness among local communities and visitors, as well as developing environmentally friendly land management practices. The proposed prevention model includes several key elements: (1) active community participation in managing ecotourism areas; (2) sustainable environmental training and education; (3) collaboration between government, private sector and society in monitoring and enforcing the law; and (4) development of ecotourism infrastructure that supports nature conservation. Implementation of this model is expected to significantly reduce the risk of forest and land fires in Riau, while encouraging economic growth through sustainable ecotourism.